السرقة العلمية وانعكاساتها على جودة التعليم العالي في ظل التحول الرقمي المتسارع - مجرالو أحلام; زاوي علي (University Of Eloued جامعة الوادي, 2023)
The phenomenon of scientific theft is one of the most important problems that threaten scientific research in Algerian universities, as the spread of this scourge has taken multiple forms and has negative effects on individuals as well as on the quality of scientific research and the status of the university. The student or university professor is one of the pillars of science and a basic base in building science and advancing the wheel of development at various levels, and that every stagnation or defect and decline in the level of intellectual production and scientific integrity would negatively affect the scientific yield of subsequent generations, and cancels the principle of quality in education.
Scientific plagiarism and its repercussions on the quality of university education in light of the accelerated digital transformation
مداخلة
Keywords: السرقة العلمية; جودة التعليم العالي; التحول الرقمي; Scientific plagiarism; quality of university education; digital transformation